Method for preparing single crystal silicon flip metasurface and flexible single crystal silicon metasurface

The described method for processing single-crystal silicon meta-surfaces addresses the complexity and instability issues in existing flexible meta-surface technologies by using hydrofluoric acid treatment and controlled aggregation, resulting in improved optical performance and integration capabilities.

CN118579720BActive Publication Date: 2025-03-14SUZHOU UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410533014.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-30
Publication Date
2025-03-14
Estimated Expiration
2044-04-30

AI Technical Summary

Technical Problem

Current methods for preparing flexible single-crystal silicon meta-surfaces are complex, result in unstable performance, and have limited scalability due to issues with material transfer, environmental sensitivity, and difficulty in achieving uniform thickness, leading to suboptimal optical properties and integration with other materials.

Method used

A method involving nanostructure processing, hydrofluoric acid treatment, and controlled aggregation of single-crystal silicon particles on flexible substrates, allowing for the formation of flat meta-surfaces that can be flipped and integrated with various materials, enabling better optical response and stability.

Benefits of technology

The method enhances the optical response and stability of flexible single-crystal silicon meta-surfaces, allowing for more efficient light interaction and improved integration with other materials, achieving performance comparable to commercial detectors while being more scalable and environmentally robust.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118579720B_ABST
    Figure CN118579720B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a single crystal silicon flip metasurface and a flexible single crystal silicon metasurface. The preparation of the single crystal silicon flip metasurface includes the following steps: coating a layer of polymer film on the surface of an SOI wafer with a micro-nano structure on the top silicon layer, immersing the SOI wafer containing the polymer film in HF, and when the middle silicon oxide layer of the SOI wafer is completely corroded by HF, immersing the SOI wafer in water, and the polymer film wrapped with a single crystal silicon nanoparticle array floats on the water surface, and the polymer film is flipped 180° and transferred to a target substrate to obtain the single crystal silicon flip metasurface. The method of the present invention is combined with wet transfer to flip the metasurface so that it is directly exposed to the air, making the surface flatter and facilitating direct integration with two-dimensional materials, quantum dots and other materials. In addition, the present invention also provides a method for preparing a flexible single crystal silicon metasurface and a single crystal silicon stacked metasurface with adjustable gap.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metasurfaces, and in particular to a method for preparing a single-crystal silicon flip metasurface and a flexible single-crystal silicon metasurface. Background Art

[0002] With the advancement of science and technology, artificial intelligence will play an increasingly important role in smart wearables, image recognition, smart cities and the Internet of Things, and these concepts are inseparable from information perception. Metasurfaces are two-dimensional metamaterials that can not only achieve sensitive perception of light fields, but also phase modulate light fields by artificially arranging specially designed sub-wavelength particles at a two-dimensional interface. Compared with traditional optical components, metasurfaces have higher efficiency and less attenuation.

[0003] Flat or rigid metasurfaces limit their use in more application scenarios, while flexible metasurfaces are ultra-thin, low modulus, and light weight, and can be applied to objects on any surface. They have great potential in the fields of bionic sensing, wearable devices, and conformal optics. In the biomedical field, flexible sensors can reflect the blood oxygen level of a large area of ​​skin in real time without relying on rigid and bulky finger-clip devices; in the field of lighting and display, flexible display screens are a hot topic of research, among which flexible OLED display technology is considered to be the most promising next-generation display technology; in the fields of conformal optics and visible light communications, the application of flexible photonic devices will undoubtedly bring a more efficient and convenient user experience.

[0004] In the existing preparation technology, the metasurface is usually transferred from the hard substrate to the flexible substrate by direct flip transfer or stamp-assisted transfer. The metasurface of the flexible photonic device prepared in this way is usually embedded in the flexible substrate, which limits the medium environment freedom of the metasurface, making it impossible to fully apply the rich light field regulation function of the metasurface. In addition, most of the existing technologies use media such as metal or amorphous silicon as the material of the nanoantenna. Metal plasmons will bring inevitable ohmic losses, while media such as amorphous silicon will increase unnecessary absorption losses, thereby limiting the optical performance. The existing flexible single-crystal silicon metasurface preparation process is complicated, which increases the difficulty of preparation and the time-consuming process, thereby limiting its large-scale production and application. In addition, the performance of the prepared flexible metasurface may be affected by environmental factors such as temperature, humidity and ultraviolet rays. These environmental factors may cause deformation and performance degradation of the metasurface, thereby affecting its long-term stability.

[0005] In 2022, Liu et al. were inspired by the wet transfer of two-dimensional materials and developed a new "water floatation" process. When the metasurface prepared by this method is integrated with a single-layer two-dimensional material, the two-dimensional material is likely to break due to poor surface flatness. In addition, it has a good effect on the transfer of small-format particle arrays, but in the transfer of large-format single-crystal silicon metasurfaces, some particles are often lost, or the shape of the original structure cannot be maintained, with a high failure rate.

[0006] In addition, in the existing wet transfer method, the metasurface after transfer can only be processed on the upper surface, and is limited by the aspect ratio of the structure surface after transfer, making it difficult to couple with other materials. In addition, in order to improve device performance, a polymer film with a refractive index close to that of the substrate needs to be coated on the metasurface after transfer to meet the phase matching condition. However, the presence of the polymer film makes it difficult to control the spacing when the metasurface after transfer is coupled with other metasurfaces. And when it is applied to silicon-based photodetectors, it is impossible to plate metal on the back of the silicon substrate, so that ohmic contact cannot be formed on its back, which limits the performance of the detector. Summary of the invention

[0007] In order to solve the above technical problems, the primary purpose of the present invention is to provide a method for preparing a single crystal silicon inverted metasurface.

[0008] A further object of the present invention is to provide a method for preparing a flexible single-crystal silicon metasurface.

[0009] The third object of the present invention is to provide a method for preparing a single crystal silicon laminated metasurface.

[0010] The above object of the present invention is achieved through the following technical solutions:

[0011] A first aspect of the present invention provides a method for preparing a single crystal silicon inversion metasurface, comprising the following steps:

[0012] Step I: nanostructuring the surface of an insulating substrate silicon wafer bonded together by a top silicon layer, a silicon oxide layer and a silicon base layer, making the top silicon layer of the insulating substrate silicon wafer into a single crystal silicon nanoparticle array, and coating a layer of polymer film on the surface of the single crystal silicon nanoparticle array, wherein the thickness of the polymer film is 500nm to 1μm, and the polymer is insoluble in water and does not react with hydrofluoric acid;

[0013] Step II: using a hydrofluoric acid solution to remove the silicon oxide layer of the insulating substrate silicon wafer;

[0014] Step III: transferring the polymer film wrapped with the single-crystalline silicon nanoparticle array and the silicon substrate layer obtained in step II into water, so that the polymer film wrapped with the single-crystalline silicon nanoparticle array floats on the water surface to be separated from the silicon substrate layer;

[0015] Step IV: turning the polymer film wrapped with the single crystal silicon nanoparticle array 180 degrees;

[0016] Step V: transferring the polymer film coated with the single-crystal silicon nanoparticle array after flipping 180° to a target substrate and drying;

[0017] Step VI: Fixing the polymer film wrapped with the single-crystal silicon nanoparticle array after flipping 180° on the target substrate by heating to obtain the single-crystal silicon flipped metasurface.

[0018] The present invention proposes a method for turning over a metasurface. This method is combined with wet transfer to turn over the metasurface so that it is directly exposed to the air, making the surface flatter and convenient for direct integration with two-dimensional materials, quantum dots and other materials. At the same time, for the nano-scale silicon film separated from the upper surface of the SOI wafer, when the upper surface of the silicon film has been plated with metal, this method can be used to turn over the back of the silicon film and plate metal again to form a Fabry-Perot cavity, forming ohmic contacts on both sides. The silicon-based photodetector prepared by this method can theoretically greatly improve the response speed of the silicon-based photodetector. Since the energy of near-infrared photons is not enough to overcome the silicon band gap (1.12eV), the metal-silicon contact in the hot electron detector can be used to form a Schottky junction to realize the absorption of the silicon-based detector in the infrared band. The Fabry-Perot cavity structure prepared by the "turning over" process can excite a strong electric field in the silicon film to induce an avalanche effect by applying a small bias voltage to the device. When a 1.9V bias is applied, the device's responsivity at the infrared communication wavelength of 1550nm reaches 0.2A / W. By adjusting the thickness of the silicon film, the narrowband peak absorption wavelength can be adjusted to 1780nm. The device's responsivity at a 3V bias reaches 0.12A / W. This is comparable to the performance of commercial detectors based on germanium and indium gallium arsenide materials.

[0019] Furthermore, in step I, the material of the top silicon layer of the insulating substrate silicon wafer is P-type single crystal silicon, with a resistivity of not less than 2kOhm·cm and a thickness of 90 to 110nm; the thickness of the silicon oxide layer is 400 to 500nm; the material of the silicon base layer is P-type single crystal silicon, with a thickness of 400 to 500μm.

[0020] Furthermore, in step I, the nanostructuring process includes: spin coating a layer of photoresist on the surface of the top silicon layer; exposing a periodic single-crystal silicon nanoparticle array pattern on the photoresist of the top silicon layer using an electron beam exposure system; and then etching using a reactive ion beam etching system to produce a single-crystal silicon nanoparticle array on the top silicon layer of the insulating substrate silicon wafer.

[0021] Furthermore, the photoresist is hydrogen silsesquioxane (HSQ) with a model number of XR-1541-004.

[0022] Further, in step I, the polymer is polymethyl methacrylate (PMMA) with a molecular weight of 950k.

[0023] Furthermore, in step II, the concentration of the hydrofluoric acid solution is 10% to 20%.

[0024] Furthermore, in step II, a surfactant is added to the hydrofluoric acid solution.

[0025] Hydrofluoric acid will gradually etch the surrounding silicon oxide layer, causing the single crystal silicon nanoparticle array to separate from the silicon substrate. Both single crystal silicon and polymer film are hydrophobic, which prevents the HF solution from penetrating into the surface of the silicon oxide layer, thereby affecting the HF etching efficiency of the SOI silicon oxide layer. Therefore, by adding a surfactant to the HF solution, its surface tension can be reduced, so that HF ​​can be adsorbed on the surface of the silicon layer, accelerating the etching process, and making it easier to separate the single crystal silicon nanoparticle array from the silicon substrate layer.

[0026] Furthermore, the surfactant is sodium alkyl sulfonate (C 12 H 25 SO3Na) and fatty alcohol ether sodium sulfate (RO(CH2CH2O) n -SO3Na) mixed solution.

[0027] Furthermore, the volume ratio of the surfactant to the hydrofluoric acid solution is 1:(200-300).

[0028] Furthermore, the volume ratio of the sodium alkyl sulfonate to the sodium fatty alcohol ether sulfate is 1:(1-2).

[0029] Furthermore, in step II, the immersion time in the hydrofluoric acid solution is 4 to 16 hours.

[0030] Further, in step II, the surface of the hydrofluoric acid solution is lower than the surface of the top silicon layer.

[0031] Furthermore, in step III, the water is ultrapure water.

[0032] Further, in step IV, the polymer film is pressed vertically downward by holding the quartz plate with tweezers and flipped 180° in water.

[0033] Furthermore, the quartz sheet has a thickness of about 0.5 to 0.6 mm and needs to be plasma cleaned before use to make its surface hydrophilic and avoid using the sharp edge of the quartz sheet to press down the film.

[0034] Further, in step V, the target substrate is a rigid substrate or a flexible substrate that is insoluble in water.

[0035] Furthermore, the rigid substrate is a quartz substrate.

[0036] Furthermore, the flexible substrate is a polydimethylsiloxane (PDMS) substrate.

[0037] Furthermore, the thickness of the PDMS substrate is 500-550 μm.

[0038] Furthermore, in step VI, for a rigid substrate, the heating temperature is 110-130° C., and the heating time is 3-5 min.

[0039] Furthermore, in step VI, for the flexible substrate, the heating temperature is 40-60° C., and the heating time is 10-20 min.

[0040] Furthermore, in step VI, the heating method is heating on a heating table.

[0041] A second aspect of the present invention provides a method for preparing a flexible single crystal silicon metasurface, comprising the following steps:

[0042] Step I: nanostructuring the surface of an insulating substrate silicon wafer bonded together by a top silicon layer, a silicon oxide layer and a silicon base layer, making the top silicon layer of the insulating substrate silicon wafer into a single crystal silicon nanoparticle array, and coating a layer of polymer film on the surface of the single crystal silicon nanoparticle array, wherein the thickness of the polymer film is 500nm to 1μm, and the polymer is insoluble in water and does not react with hydrofluoric acid;

[0043] Step II: using a hydrofluoric acid solution to remove the silicon oxide layer of the insulating substrate silicon wafer;

[0044] Step III: transferring the polymer film wrapped with the single-crystalline silicon nanoparticle array and the silicon substrate layer obtained in step II into water, so that the polymer film wrapped with the single-crystalline silicon nanoparticle array floats on the water surface to be separated from the silicon substrate layer;

[0045] Step IV: transferring the polymer film encapsulating the single crystal silicon nanoparticle array onto a flexible substrate and drying it;

[0046] Step V: fixing the single crystal silicon nanoparticle array on the flexible substrate by heating;

[0047] Step VI: Use an organic solvent to remove the polymer film to obtain the flexible single-crystal silicon metasurface.

[0048] The present invention first performs micro-nano processing on a single crystal silicon film to form a single crystal silicon nanoparticle array. Because single crystal silicon has a high refractive index (n=3.7) and a low absorption coefficient (k<0.01) in the visible light band, the present invention selects single crystal silicon as the material for preparing a metasurface, which is most suitable for preparing high-quality optical nanoantennas, and can simultaneously support electric and magnetic Mie resonances, thereby enhancing the interaction between light and matter. Subsequently, a polymer solution is spin-coated on the surface of the single crystal silicon nanoparticle array to form a polymer film wrapped with the single crystal silicon nanoparticle array. Next, the silicon oxide layer is etched away by HF, and the reaction equation of HF and silicon oxide is: 4HF+SiO2=2H2O+SiF4. When the middle silicon oxide layer of the insulating substrate silicon wafer is completely etched by hydrofluoric acid, the silicon base layer and the polymer film wrapped with the single crystal silicon nanoparticle array are transferred to water. In this process, the single crystal silicon nanoparticle array floats on the water surface under the wrapping of the polymer film. This polymer film can not only constrain the single-crystalline silicon nanoparticle array to maintain its shape, but also help separate the single-crystalline silicon nanoparticle array from the silicon substrate layer. The polymer film wrapped with the single-crystalline silicon nanoparticle array floating on the water surface can be transferred to any target substrate that is insoluble in water. After the metasurface is prepared, the target substrate is heat-treated to completely remove the water vapor between the single-crystalline silicon nanoparticle array and the target substrate, improve the contact between the single-crystalline silicon nanoparticle array and the target substrate, and the electrostatic force between the single-crystalline silicon nanoparticle array and the target substrate makes them adhere more firmly together.

[0049] The present invention solves the technical problems that the preparation process of the existing flexible single-crystal silicon metasurface is complicated and the performance and stability of the prepared flexible single-crystal silicon metasurface are poor. The flexible device made of the single-crystal silicon metasurface under the preparation method can conform to the substrate, bring better optical response, and have more control freedom. At the same time, the flexible photonic device constructed by utilizing the high refractive index and low absorption loss characteristics of the single-crystal silicon particle array has theoretically better optical response and lower absorption loss than amorphous silicon and metal particles.

[0050] The present invention also solves the problem that the existing wet transfer can only transfer small-format thin films (hundreds of micrometers). By controlling the thickness of the polymer film and the concentration of hydrofluoric acid, the present invention can be used to transfer larger-format (centimeter-level) single-crystal silicon metasurfaces with a more stable success rate and repeatability.

[0051] In addition, when transferring the polymer film wrapped with the single crystal silicon nanoparticle array to the flexible substrate, its flatness needs to be maintained. The inventors found that in the process of wet transfer, the thickness of the film is the most critical factor affecting the wet transfer result. This may be because the hardness of the polymer is positively correlated with the thickness. When the silicon oxide under the polymer film is etched by HF acid, the thicker polymer film should be able to maintain a better original state. However, when the thickness of the polymer film is too thick, it is more likely to cause inconsistent film thickness, thereby causing uneven internal stress during the thermal curing process, which will affect the overall flatness of the film after curing. In order to ensure the flatness of the film in order to transfer large-format single crystal silicon particle arrays, the thickness of the polymer film is preferably 500nm~1μm.

[0052] Furthermore, in step I, the material of the top silicon layer of the insulating substrate silicon wafer is P-type single crystal silicon, with a resistivity of not less than 2kOhm·cm and a thickness of 90 to 110nm; the thickness of the silicon oxide layer is 400 to 500nm; the material of the silicon base layer is P-type single crystal silicon, with a thickness of 400 to 500μm; and the polymer is polymethyl methacrylate (PMMA) with a molecular weight of 950k.

[0053] Furthermore, in step I, the nanostructuring process includes: spin coating a layer of photoresist on the surface of the top silicon layer; exposing a periodic single-crystal silicon nanoparticle array pattern on the photoresist of the top silicon layer using an electron beam exposure system; and then etching using a reactive ion beam etching system to produce a single-crystal silicon nanoparticle array on the top silicon layer of the insulating substrate silicon wafer.

[0054] Furthermore, the photoresist is hydrogen silsesquioxane (HSQ) with a model number of XR-1541-004.

[0055] Furthermore, in step II, the concentration of the hydrofluoric acid solution is 10% to 20%.

[0056] Furthermore, in step II, a surfactant is added to the hydrofluoric acid solution.

[0057] Furthermore, the surfactant is sodium alkyl sulfonate (C 12 H 25 SO3Na) and fatty alcohol ether sodium sulfate (RO(CH2CH2O) n -SO3Na) mixed solution.

[0058] Furthermore, the volume ratio of the surfactant to the hydrofluoric acid solution is 1:(200-300).

[0059] Furthermore, the volume ratio of the sodium alkyl sulfonate to the sodium fatty alcohol ether sulfate is 1:(1-2).

[0060] Furthermore, in step II, the immersion time in the hydrofluoric acid solution is 4 to 16 hours.

[0061] Furthermore, in step III, the water is ultrapure water.

[0062] Furthermore, in step IV, the flexible substrate is a polydimethylsiloxane (PDMS) substrate.

[0063] Furthermore, the thickness of the PDMS substrate is 500-550 μm.

[0064] Furthermore, in step V, the heating temperature is 40-60° C., and the heating time is 10-20 min.

[0065] Furthermore, in step V, the heating method is heating on a heating table.

[0066] Furthermore, in step VI, the organic solvent is anhydrous ethanol or acetone.

[0067] Furthermore, in step VI, a plasma cleaning machine is used to clean and remove the organic solvent remaining on the surface, and the cleaning time is 5 to 10 minutes.

[0068] A third aspect of the present invention provides a method for preparing a single crystal silicon stacked metasurface, comprising the following steps:

[0069] Step I: Take a single crystal silicon flip metasurface based on a rigid substrate prepared by the method described in the first aspect of the present invention and a single crystal silicon flip metasurface based on a flexible substrate prepared by the method described in the first aspect of the present invention, and adjust the angles of the two layers of single crystal silicon flip metasurfaces;

[0070] Step II: superimposing the single-crystal silicon flip metasurface based on a flexible substrate on the single-crystal silicon flip metasurface based on a rigid substrate to obtain a stacked single-crystal silicon metasurface;

[0071] Step III: heating the stacked single crystal silicon metasurface, removing the flexible substrate, and obtaining the single crystal silicon stacked metasurface.

[0072] Furthermore, in step II, when superimposing the single-crystal silicon flip metasurface based on a flexible substrate, the rotation angle of the two layers of the metasurface in the micro-area needs to be determined, and the metasurface needs to contain angle alignment marks so that the rotation angle of the two layers of the metasurface can be determined under a microscope.

[0073] Furthermore, step II also includes the step of adding a dielectric material on the single crystal silicon flip metasurface based on the rigid substrate.

[0074] Furthermore, in step III, the heating temperature is 110-130° C., and the heating time is 3-5 min.

[0075] Furthermore, in step III, when the single crystal silicon is flipped and the metastructure surface is superimposed, it needs to be lowered until it fits perfectly before subsequent heating is carried out.

[0076] The present invention proposes a method for stacking two layers of metasurfaces with adjustable gaps, by turning over the metasurfaces during the transfer process so that the tops of the two layers of metasurfaces are exposed to the air, and flexible conformal stacking of two layers of metasurfaces with adjustable gaps is performed. Different dielectric spacer materials are spin-coated during this process, and the interlayer thickness can be changed from 0 to achieve the purpose of improving the optical performance of the device. At the same time, the stacking angle between the two layers of metasurfaces can be freely adjusted, which improves the spatial design freedom of the flexible metasurface. By combining two independently designed metasurfaces, it is possible to achieve a more diverse regulation of light field characteristics.

[0077] Beneficial effects of the present invention:

[0078] The present invention proposes a method for turning over a metasurface. This method, combined with wet transfer, can turn over the metasurface to expose it directly to the air, making the surface flatter and facilitating direct integration with two-dimensional materials, quantum dots and other materials.

[0079] The present invention solves the technical problems that the preparation process of the existing flexible single-crystal silicon metasurface is complicated and the performance and stability of the prepared flexible single-crystal silicon metasurface are poor. The flexible device made of the single-crystal silicon metasurface under the preparation method can conform to the substrate, bring better optical response, and have more control freedom. At the same time, the flexible photonic device constructed by utilizing the high refractive index and low absorption loss characteristics of the single-crystal silicon particle array has theoretically better optical response and lower absorption loss than amorphous silicon and metal particles.

[0080] The present invention also solves the problem that the existing wet transfer can only transfer small-format thin films (hundreds of micrometers). By controlling the thickness of the polymer film and the concentration of hydrofluoric acid, the present invention can be used to transfer larger-format (centimeter-level) single-crystal silicon metasurfaces with a more stable success rate and repeatability.

[0081] The present invention proposes a method for stacking two layers of metasurfaces with adjustable gaps, by turning over the metasurfaces during the transfer process so that the tops of the two layers of metasurfaces are exposed to the air, and flexible conformal stacking of two layers of metasurfaces with adjustable gaps is performed. Different dielectric spacer materials are spin-coated during this process, and the interlayer thickness can be changed from 0 to achieve the purpose of improving the optical performance of the device. At the same time, the stacking angle between the two layers of metasurfaces can be freely adjusted, which improves the spatial design freedom of the flexible metasurface. By combining two independently designed metasurfaces, it is possible to achieve a more diverse regulation of light field characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0082] Figure 1 This is a flow chart of the method for preparing the flexible single-crystal silicon metasurface of Example 1.

[0083] Figure 2 This is a scanning electron microscope image of the single-crystalline silicon nanoparticle array prepared by nanostructuring treatment on the top silicon layer in Example 1.

[0084] Figure 3 This is an optical picture of the polymer film encapsulating the single-crystalline silicon nanoparticle array transferred to the PDMS substrate obtained in step IV of Example 1.

[0085] Figure 4 This is the reflection spectrum of the flexible single-crystal silicon metasurface prepared in Example 1 before and after stretching.

[0086] Figure 5 This is a flow chart of the method for preparing the single crystal silicon inverted metasurface of Example 4.

[0087] Figure 6 This is an AFM scan of the single-crystal silicon flipped meta-structure surface of Example 4.

[0088] Figure 7 Spectra of the single-crystal silicon metasurface and the single-crystal silicon flipped metasurface of Example 4 under normal incidence.

[0089] Figure 8 Schematic diagrams and optical microscope images of the single-crystal silicon metasurface and the flexible single-crystal silicon flipped metasurface of Example 4, as well as extinction spectra of samples with two different particle array diameters.

[0090] Fig. 9 This is a flow chart of the method for preparing the single-crystal silicon laminated metasurface of Example 6.

[0091] Fig.10 These are SEM images of the PMMA film coated with a single-crystalline silicon nanoparticle array prepared in step IV in Examples 2 to 3 and Comparative Examples 1 to 2; wherein (a) is Example 2; (b) is Example 3; (c) is Comparative Example 2; and (d) is Comparative Example 3.

[0092] Fig.11 Surface images of the flexible single-crystal silicon metastructures prepared in Example 1 and Comparative Example 3.

[0093] Wherein: 11 is a plastic culture dish, 12 is a silicon base layer, 13 is a polymer film wrapped with a single-crystal silicon nanoparticle array, 14 is a silicon oxide layer, 15 is hydrofluoric acid, 16 is ultrapure water, 17 is a PDMS substrate, 18 is a heating stage, 19 is a quartz sheet, and 20 is a quartz substrate. DETAILED DESCRIPTION

[0094] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0095] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0096] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.

[0097] Example 1

[0098] A method for preparing a flexible single-crystal silicon metasurface comprises the following steps:

[0099] Step I: nanostructure the surface of an insulating substrate silicon wafer bonded with a top silicon layer, a silicon oxide layer and a silicon base layer, spin-coat a layer of photoresist (HSQ with model number XR-1541-004) on the surface of the top silicon layer; use an electron beam exposure system to expose a periodic single-crystal silicon nanoparticle array pattern on the photoresist of the top silicon layer; then etch through a reactive ion beam etching system to make a single-crystal silicon nanoparticle array on the top silicon layer of an insulating substrate silicon wafer (SOI), use a plasma cleaner to clean for 5 minutes to ensure that the SOI wafer is as clean as possible and the edge of the SOI wafer has a certain degree of hydrophilicity; coat a layer of PMMA (molecular weight 950k) film with a thickness of 500nm on the surface of the single-crystal silicon nanoparticle array, heat the spin-coated PMMA film at 180°C for 90 seconds using a hot plate, and after the SOI wafer cools, use tweezers to draw a circle along the periphery of the particle array on the PMMA film to frame the particle array to be transferred. Among them, the top silicon layer of the insulating substrate silicon wafer is made of P-type single crystal silicon, with a resistivity of 2kOhm·cm and a thickness of 100nm; the thickness of the silicon oxide layer is 450nm; and the material of the silicon base layer is P-type single crystal silicon, with a thickness of 450μm.

[0100] Step II: Take a plastic culture dish, place the treated SOI sheet in the middle of the culture dish, and use a dropper to absorb 16% HF acid (add sodium alkyl sulfonate (C 12 H 25 SO3Na) and fatty alcohol ether sodium sulfate (RO(CH2CH2O) n -SO3Na) mixed solution, sodium alkyl sulfonate (C 12 H 25SO3Na) and fatty alcohol ether sodium sulfate (RO(CH2CH2O) n -SO3Na) mixed solution and HF acid (volume ratio is 1:200) drip the petri dish along the periphery of the SOI wafer, make sure that the HF acid does not cover the SOI wafer, but is flush with the SOI wafer, to avoid HF acid residue on the surface of the polymer film, and then cover the plastic dish cover. During the HF acid etching of the SOI wafer, ensure that the environment is stable, the humidity is kept below 50%, and the HF acid etching time is controlled within 4 hours.

[0101] Step III: Before the HF acid wet etching is completed, prepare the tools for wet transfer. During the transfer process, use plastic tweezers to hold both ends of the SOI sheet and press it into ultrapure water at a 30° angle to ensure that the PMMA film in the framed area around the particle array has been separated from the SOI sheet. Then continue to press the SOI sheet into ultrapure water until the PMMA film wrapped with the single-crystalline silicon nanoparticle array is completely separated from the SOI sheet. At this time, the PMMA film wrapped with the single-crystalline silicon nanoparticle array should float on the surface of ultrapure water.

[0102] Step IV: Use the PDMS substrate as the salvage substrate. Before the wet transfer, since the PDMS substrate is flexible and not easy to salvage, spread the PDMS substrate flatly on a glass sheet, clean it with a plasma cleaner for 5 minutes to make its surface hydrophilic, and then use it for salvage. Salvage the PMMA film wrapped with a single-crystal silicon nanoparticle array floating on the ultrapure water and transfer it to the PDMS substrate, waiting for the water to evaporate completely.

[0103] Step V: After the PMMA film is tightly attached to the PDMS substrate, if you want to replace the PMMA dielectric layer above the particle array, you need to first fix the particle array on the PDMS substrate by heating. The heating method is to heat it on a heating table at 50°C for 15 minutes. If the temperature is too high, the PDMS will expand thermally and affect the surface flatness.

[0104] Step VI: Use wet etching to remove the PMMA film on the surface of the particle array. Use a syringe to absorb an appropriate amount of acetone solution and drop a few drops on the surface of the PMMA film. After one minute, use another syringe to absorb the waste liquid. Repeat this process three times to completely remove the PMMA film on the single-crystal silicon nanoparticle array. Then use a plasma cleaner to clean the PDMS substrate with the single-crystal silicon nanoparticle array for 5 minutes to remove the residual organic solvent and obtain a flexible single-crystal silicon metasurface.

[0105] The process flow chart of the method for preparing the flexible single crystal silicon metasurface of Example 1 is as follows: Figure 1 As shown, the scanning electron microscope image of the single crystal silicon nanoparticle array prepared by nanostructuring treatment on the top silicon layer in Example 1 is as follows Figure 2 shown.

[0106] The optical image of the polymer film coated with the single crystal silicon nanoparticle array transferred to the PDMS substrate obtained in step IV of Example 1 is as follows: Figure 3 As shown, the left picture is the overall and local magnified photos of the large-format polymer film wrapped with single-crystalline silicon nanoparticle arrays transferred to the PDMS substrate, and the right picture is a microscope bright field photo of the polymer film wrapped with single-crystalline silicon nanoparticle arrays at 100X. Figure 3 It can be seen that in the actual photos of the two single-crystalline silicon particle arrays transferred to the PDMS substrate, the side length of each particle array is 1.2 mm, the polymer film wrapped with the two single-crystalline silicon nanoparticle arrays has a centimeter-level format, and the film as a whole is very flat, so this method actually has the ability to transfer centimeter-level format particle arrays.

[0107] The reflection spectra of the flexible single crystal silicon metasurface prepared in Example 1 before and after stretching are as follows: Figure 4 As shown, the left figure is the data before stretching, and the right figure is the data after stretching. For a flexible single-crystal silicon large-format metasurface containing single-crystal silicon particles with a diameter of 530nm, a lateral period of 600nm, and a longitudinal period of 800nm, when the lateral period is stretched from 590nm to 640nm, the reflection spectrum change curve at a collection angle of 18°, the dotted line is the simulation data, and the solid line is the experimental data. The consistency of the peak position of the simulation and experimental data shows that when the flexible metasurface prepared in the experiment is dynamically stretched, the lattice will also be stretched together, which is consistent with expectations, further illustrating the reliability of the preparation method of the present invention.

[0108] During the dynamic stretching process, due to the material properties of PDMS, its deformation is recoverable. After wrapping the single-crystal silicon nanoparticle array, the stretching process will not affect the performance of the particle array. In addition, the present invention has tested and found that after the flexible single-crystal silicon metasurface prepared in Example 1 is exposed to the air for a long time, the structural color of the single-crystal silicon nanoparticle array does not change, indicating that its structural parameters are not affected, proving that the flexible single-crystal silicon metasurface prepared in the present invention has long-term stability.

[0109] Example 2

[0110] A method for producing a flexible single crystal silicon metasurface is basically the same as that of Example 1, except that the immersion time in step II is 7 hours.

[0111] Example 3

[0112] A method for producing a flexible single crystal silicon metasurface is basically the same as that of Example 1, except that the immersion time in step II is 16 hours.

[0113] Example 4

[0114] A method for preparing a single crystal silicon inversion metasurface comprises the following steps:

[0115] Step I: nanostructure the surface of an insulating substrate silicon wafer bonded with a top silicon layer, a silicon oxide layer and a silicon base layer, spin-coat a layer of photoresist (HSQ with model number XR-1541-004) on the surface of the top silicon layer; use an electron beam exposure system to expose a periodic single-crystal silicon nanoparticle array pattern on the photoresist of the top silicon layer; then etch through a reactive ion beam etching system to make a single-crystal silicon nanoparticle array on the top silicon layer of an insulating substrate silicon wafer (SOI), use a plasma cleaner to clean for 5 minutes to ensure that the SOI wafer is as clean as possible and the edge of the SOI wafer has a certain degree of hydrophilicity; coat a layer of PMMA (molecular weight 950k) film with a thickness of 500nm on the surface of the single-crystal silicon nanoparticle array, heat the spin-coated PMMA film at 180°C for 90 seconds using a hot plate, and after the SOI wafer cools, use tweezers to draw a circle along the periphery of the particle array on the PMMA film to frame the particle array to be transferred. Among them, the top silicon layer of the insulating substrate silicon wafer is made of P-type single crystal silicon, with a resistivity of 2kOhm·cm and a thickness of 100nm; the thickness of the silicon oxide layer is 450nm; and the material of the silicon base layer is P-type single crystal silicon, with a thickness of 450μm.

[0116] Step II: Take a plastic culture dish, place the treated SOI sheet in the middle of the culture dish, and use a dropper to absorb 16% HF acid (add sodium alkyl sulfonate (C 12 H 25 SO3Na) and fatty alcohol ether sodium sulfate (RO(CH2CH2O) n -SO3Na) mixed solution, sodium alkyl sulfonate (C 12 H 25 SO3Na) and fatty alcohol ether sodium sulfate (RO(CH2CH2O) n -SO3Na) mixed solution and HF acid (volume ratio is 1:200) drip the petri dish along the periphery of the SOI wafer, make sure that the HF acid does not cover the SOI wafer, but is flush with the SOI wafer, to avoid HF acid residue on the surface of the polymer film, and then cover the plastic dish cover. During the HF acid etching of the SOI wafer, ensure that the environment is stable, the humidity is kept below 50%, and the HF acid etching time is controlled within 4 hours.

[0117] Step III: Before the HF acid wet etching is completed, prepare the tools for wet transfer. During the transfer process, use plastic tweezers to hold both ends of the SOI sheet and press it into ultrapure water at a 30° angle to ensure that the PMMA film in the framed area around the particle array has been separated from the SOI sheet. Then continue to press the SOI sheet into ultrapure water until the PMMA film wrapped with the single-crystalline silicon nanoparticle array is completely separated from the SOI sheet. At this time, the PMMA film wrapped with the single-crystalline silicon nanoparticle array should float on the surface of ultrapure water.

[0118] Step IV: Use tweezers to hold the quartz plate and press the PMMA film wrapped with the single-crystalline silicon nanoparticle array vertically downward and flip it 180° in the water. After flipping, the PMMA film wrapped with the single-crystalline silicon nanoparticle array floats to the water surface again under the action of water buoyancy.

[0119] Step V: Using a quartz substrate as a salvaged substrate, the PMMA film wrapped with the single-crystal silicon nanoparticle array is salvaged and transferred to the quartz substrate after being flipped 180°, and the water is waited for complete evaporation.

[0120] Step VI: Fix the PMMA film wrapped with the single-crystal silicon nanoparticle array after flipping 180° on the quartz substrate by heating at 120°C on a heating table for 5 minutes to obtain a single-crystal silicon flipped metasurface based on the quartz substrate.

[0121] The flow chart of the method for preparing the single crystal silicon flip metasurface of Example 4 is as follows: Figure 5 As shown, the atomic force microscope (AFM) scanning image of the single crystal silicon flip metastructure surface of Example 4 is as follows Figure 6 shown.

[0122] The extinction spectra of the single crystal silicon metasurface (prepared in the same manner as in Example 4, except that no flipping is performed in step IV) and the single crystal silicon flipped metasurface in Example 4 under normal incidence are shown in FIG. Figure 7 As shown, the dotted line is the extinction spectrum of the flipped single-crystal silicon metasurface, and the solid line is the extinction spectrum of the flipped single-crystal silicon metasurface, where the particle array diameter is 100nm and the period is 405nm. The extinction spectrum proves that there are indeed different regulatory effects on the light field before and after the flip. Before and after the flip, the change from silicon / quartz to silicon / air leads to a decrease in the effective refractive index, which further leads to a blue shift in the surface lattice resonance wavelength and a decrease in the corresponding resonance peak.

[0123] Coupling with two-dimensional materials requires a flat structure to maintain its inherent optical properties. Two-dimensional materials are very flat, and the flatness of the coupling substrate is very high. By flipping the film over, the flatter bottom surface of the film can be integrated with the two-dimensional material, protecting the fragile and easily broken two-dimensional material. The complete two-dimensional material is directly integrated with the bottom of the particle array exposed after flipping, which can better exert the optical properties of the two-dimensional material.

[0124] Therefore, the present invention prepares a single-crystal silicon nanoparticle array that is turned over and faces the air, and its surface is almost flat (roughness: 3.3±0.7nm). Figure 8 Schematic diagrams and optical microscope images of samples of a single-crystal silicon metasurface (the preparation method is basically the same as that of Example 4, the difference being that no flipping is performed in step IV) and the single-crystal silicon flipped metasurface of Example 4, as well as extinction spectra of samples with two different particle array diameters. Among them, a is a schematic diagram of the sample cross-section of the single-crystal silicon metasurface and the single-crystal silicon flipped metasurface of Example 4 and a bright-field microscope image from a top-down perspective, scale bar: 50μm, the sample on the left corresponds to single-crystal silicon (c-Si) nanoparticles facing the air (marked as Si / air), and the sample on the right corresponds to nanoparticles (Si / quartz) directly located on top of quartz; b is the extinction spectrum of a sample with a particle array diameter of 100nm, the inclined dotted line indicates the change with the array period, and c is the extinction spectrum of a sample with a particle array diameter of 130nm. As shown Figure 8 As shown in Figure 1, both nanoparticle arrays are wrapped in PMMA films, and the structures of the two samples are mirror-symmetrical due to the flipping process during the wet transfer fabrication process. Figure 8 As can be seen in Figure a, by changing the dielectric environment directly facing the nanoparticle array from air to quartz, the structural color of the particle array shows obvious differences. Figure 8 Figures b and c compare the extinction spectra of single-crystal silicon flipped metasurface samples with two different particle array diameters. The dashed and solid lines represent the extinction spectra of the nanoparticle array facing the air (after flipping) and adhering to quartz (not flipped), respectively. The change from silicon / air to silicon / quartz before and after flipping leads to an increase in the effective refractive index, which further causes a red shift in the surface lattice resonance. This change is more significant for nanoparticle arrays with larger diameters. Spectral characterization confirms the successful preparation of nanoparticle arrays with flat surfaces, providing an ideal platform for integrating two-dimensional materials on top.

[0125] The present invention realizes the operation of turning over the film on the water surface, and can directly integrate the metasurface with quantum light sources such as quantum dots, dye molecules or direct bandgap semiconductors. The active light-emitting metasurface realized by this method can flexibly control the resonant wavelength, spectrum width, near-field enhancement multiple, and far-field radiation characteristics of the metasurface. In addition, it has the characteristics of micro-integration, flexibility, and large size, and can be used in fields such as high-definition display solid-state lighting. At the same time, this operation turns over the metasurface wrapped by the polymer (PMMA) and directly exposes the metasurface to the air, which can achieve the effect of accurately regulating the coupling spacing when coupling metasurfaces on two different planes. By regulating the spacing, achromatic and non-reflective metasurfaces can be achieved, paving the way for the realization of photonic devices with designable transmission or absorption spectra and not affected by reflection. Such non-reflective photonic devices can be used in sensing, stealth and other aspects in the future.

[0126] Example 5

[0127] A method for preparing a single crystal silicon inversion metasurface comprises the following steps:

[0128] Step I: nanostructure the surface of an insulating substrate silicon wafer bonded with a top silicon layer, a silicon oxide layer and a silicon base layer, spin-coat a layer of photoresist (HSQ with model number XR-1541-004) on the surface of the top silicon layer; use an electron beam exposure system to expose a periodic single-crystal silicon nanoparticle array pattern on the photoresist of the top silicon layer; then etch through a reactive ion beam etching system to make a single-crystal silicon nanoparticle array on the top silicon layer of an insulating substrate silicon wafer (SOI), use a plasma cleaner to clean for 5 minutes to ensure that the SOI wafer is as clean as possible and the edge of the SOI wafer has a certain degree of hydrophilicity; coat a layer of PMMA (molecular weight 950k) film with a thickness of 500nm on the surface of the single-crystal silicon nanoparticle array, heat the spin-coated PMMA film at 180°C for 90 seconds using a hot plate, and after the SOI wafer cools, use tweezers to draw a circle along the periphery of the particle array on the PMMA film to frame the particle array to be transferred. Among them, the top silicon layer of the insulating substrate silicon wafer is made of P-type single crystal silicon, with a resistivity of 2kOhm·cm and a thickness of 100nm; the thickness of the silicon oxide layer is 450nm; and the material of the silicon base layer is P-type single crystal silicon, with a thickness of 450μm.

[0129] Step II: Take a plastic culture dish, place the treated SOI sheet in the middle of the culture dish, and use a dropper to absorb 16% HF acid (add sodium alkyl sulfonate (C 12 H 25 SO3Na) and fatty alcohol ether sodium sulfate (RO(CH2CH2O) n -SO3Na) mixed solution, sodium alkyl sulfonate (C 12 H 25SO3Na) and fatty alcohol ether sodium sulfate (RO(CH2CH2O) n -SO3Na) mixed solution and HF acid (volume ratio is 1:200) drip the petri dish along the periphery of the SOI wafer, make sure that the HF acid does not cover the SOI wafer, but is flush with the SOI wafer, to avoid HF acid residue on the surface of the polymer film, and then cover the plastic dish cover. During the HF acid etching of the SOI wafer, ensure that the environment is stable, the humidity is kept below 50%, and the HF acid etching time is controlled within 4 hours.

[0130] Step III: Before the HF acid wet etching is completed, prepare the tools for wet transfer. During the transfer process, use plastic tweezers to hold both ends of the SOI sheet and press it into ultrapure water at a 30° angle to ensure that the PMMA film in the framed area around the particle array has been separated from the SOI sheet. Then continue to press the SOI sheet into ultrapure water until the PMMA film wrapped with the single-crystalline silicon nanoparticle array is completely separated from the SOI sheet. At this time, the PMMA film wrapped with the single-crystalline silicon nanoparticle array should float on the surface of ultrapure water.

[0131] Step IV: Use tweezers to hold the quartz plate and press the PMMA film wrapped with the single-crystalline silicon nanoparticle array vertically downward and flip it 180° in the water. After flipping, the PMMA film wrapped with the single-crystalline silicon nanoparticle array floats to the water surface again under the action of water buoyancy.

[0132] Step V: Using the PDMS substrate as a salvage substrate, the PMMA film wrapped with the single-crystal silicon nanoparticle array is flipped 180° and transferred to the PDMS substrate, and the water is allowed to evaporate completely.

[0133] Step VI: Fix the PMMA film wrapped with the single-crystal silicon nanoparticle array on the PDMS substrate by heating after flipping 180°. The heating method is to heat it on a heating table at 50°C for 15 minutes to obtain a single-crystal silicon flipped metasurface based on the PDMS substrate.

[0134] Example 6

[0135] A method for preparing a single crystal silicon stacked metasurface comprises the following steps:

[0136] Step I: Take the single crystal silicon flip metasurface based on quartz substrate prepared in Example 4 and a layer of single crystal silicon flip metasurface based on PDMS substrate prepared in Example 5, and adjust the angles of the two layers of single crystal silicon flip metasurfaces; a layer of dielectric material with a known thickness can be added above the obtained metasurface film of quartz substrate to control the gap between the two particle arrays.

[0137] Step II: Determine the rotation angle of the two metasurfaces in the micro-area, and slowly superimpose the flexible single-crystal silicon metasurface based on the PDMS substrate on the single-crystal silicon flip metasurface based on the quartz substrate, so that the two metasurfaces can be conformal and stacked;

[0138] Step III: Heat the stacked single-crystal silicon metastructure surface. The PDMS film will lose its viscosity due to its pyrolysis. Slowly peel off the PDMS film to obtain the single-crystal silicon stacked metastructure surface.

[0139] The process flow chart of the method for preparing the single crystal silicon stacked metasurface of Example 6 is as follows: Fig. 9 shown.

[0140] Comparative Example 1

[0141] A method for forming a flexible single crystal silicon metasurface is basically the same as that of Example 2, except that in step I, the thickness of the PMMA film is 250 nm.

[0142] Comparative Example 2

[0143] A method for forming a flexible single crystal silicon metasurface is basically the same as that of Example 3, except that in step I, the thickness of the PMMA film is 250 nm.

[0144] The PMMA film coated with the single crystal silicon nanoparticle array prepared in step IV of Examples 2 to 3 and Comparative Examples 1 to 2 was characterized by scanning electron microscopy (SEM). Fig.10 As shown in the figure, the thicker PMMA film can maintain a better morphology after transfer, which is consistent with the prediction before the experiment. The effect of long-term immersion in HF acid on the PMMA film is not as great as the effect of changing the film thickness. However, HF acid is a strong acid that is very volatile. Although HF acid has been diluted in the experiment, long-term HF acid volatilization poses a safety hazard, and long-term immersion will also cause a large amount of water vapor to accumulate in the plastic culture dish, affecting the quality of the film. Therefore, it can be preliminarily concluded that in the process of wet transfer, the thickness of the film is the most critical factor affecting the results of wet transfer.

[0145] Comparative Example 3

[0146] A method for producing a flexible single crystal silicon metasurface is basically the same as that of Example 1, except that in step V, the heating temperature is 160°C.

[0147] The flexible single crystal silicon metasurfaces prepared in Example 1 and Comparative Example 3 are as follows: Fig.11 As shown, the left picture is comparative example 3, and the right picture is example 1. When the prior art is used for transfer, when the heat fixing temperature is 160°C, the PDMS exhibits irreversible wrinkles, while when heat fixed at 50°C, the PDMS exhibits no obvious wrinkles.

[0148] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a single crystal silicon laminated metasurface, characterized in that: The following steps are involved: Step 1: Take a layer of single-crystal silicon flip metasurface based on a rigid substrate prepared by the preparation method of single-crystal silicon flip metasurface and a layer of single-crystal silicon flip metasurface based on a flexible substrate prepared by the preparation method of single-crystal silicon flip metasurface, and adjust the angles of the two layers of single-crystal silicon flip metasurfaces; Step 2: superimposing the single-crystal silicon flip metasurface based on a flexible substrate on the single-crystal silicon flip metasurface based on a rigid substrate to obtain a stacked single-crystal silicon metasurface; Step 3: heating the stacked single crystal silicon metasurface, removing the flexible substrate, and obtaining the single crystal silicon stacked metasurface; The method for preparing the single crystal silicon inversion metasurface comprises the following steps: Step I: nanostructuring the surface of an insulating substrate silicon wafer bonded together by a top silicon layer, a silicon oxide layer and a silicon base layer, making the top silicon layer of the insulating substrate silicon wafer into a single crystal silicon nanoparticle array, and coating a layer of polymer film on the surface of the single crystal silicon nanoparticle array, wherein the thickness of the polymer film is 500 nm to 1 μm, and the polymer is insoluble in water and does not react with hydrofluoric acid; Step II: using a hydrofluoric acid solution to remove the silicon oxide layer of the insulating substrate silicon wafer; Step III: transferring the polymer film wrapped with the single-crystalline silicon nanoparticle array and the silicon substrate layer obtained in step II into water, so that the polymer film wrapped with the single-crystalline silicon nanoparticle array floats on the water surface to be separated from the silicon substrate layer; Step IV: turning the polymer film wrapped with the single crystal silicon nanoparticle array 180 degrees; Step V: transferring the polymer film wrapped with the single-crystal silicon nanoparticle array after flipping 180° to a target substrate, and drying the target substrate; the target substrate is a rigid substrate or a flexible substrate that is insoluble in water; Step VI: fixing the polymer film wrapped with the single-crystal silicon nanoparticle array after flipping 180° on the target substrate by heating to obtain the single-crystal silicon flipped metasurface; For a rigid substrate, the heating temperature is 110-130°C; for a flexible substrate, the heating temperature is 40-60°C.

2. The preparation method according to claim 1, characterized in that In step I, the top silicon layer of the insulating substrate silicon wafer is made of P-type single crystal silicon, with a resistivity of not less than 2 kOhm•cm and a thickness of 90~110 nm; the thickness of the silicon oxide layer is 400~500 nm; and the silicon base layer is made of P-type single crystal silicon with a thickness of 400~500 μm.

3. The preparation method according to claim 1, characterized in that: In step I, the polymer is polymethyl methacrylate.

4. The preparation method according to claim 1, characterized in that: In step II, a surfactant is added to the hydrofluoric acid solution, and the surfactant is a mixture of sodium alkyl sulfonate and sodium fatty alcohol ether sulfate.

5. The preparation method according to claim 1, characterized in that: Step 2 also includes the step of adding a dielectric material on the single crystal silicon inverted metasurface based on the rigid substrate.

Citation Information

Patent Citations

  • Preparation and characterization method of flexible multilayer film metamaterial based on hot-pressing process

    CN111572127A

  • Preparation method of metasurface or composite fluorescent dye metasurface

    CN114956089A

  • Method of liquid-mediated pattern transfer and device structure formed by liquid-mediated pattern transfer

    US20230166965A1